2015
DOI: 10.1177/1535370215570202
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant rat CC16 protein inhibits LPS-induced MMP-9 expression via NF-κB pathway in rat tracheal epithelial cells

Abstract: Clara cell protein (CC16) is a well-known anti-inflammatory protein secreted by the epithelial Clara cells of the airways. It is involved in the development of airway inflammatory diseases such as chronic obstructive pulmonary disease and asthma. Previous studies suggest that CC16 gene transfer suppresses expression of interleukin (IL)-8 in bronchial epithelial cells. However, its role in the function of these cells during inflammation is not well understood. In this study, we evaluated the effect of CC16 on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 64 publications
(82 reference statements)
3
31
0
Order By: Relevance
“…rCC16 protein was prepared according to published procedures [13]. Briefly, the open reading frame of rat CC16 gene was amplified and cloned into the pET-30a(+) vector (Novagen, Darmstadt, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…rCC16 protein was prepared according to published procedures [13]. Briefly, the open reading frame of rat CC16 gene was amplified and cloned into the pET-30a(+) vector (Novagen, Darmstadt, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…To further determine the differential expression patterns of these proteins in RTE cells cultured in the absence or presence of LPS and rCC16, RT-qPCR was performed for transcriptional analyses of the differentially expressed proteins at the mRNA level, (with the exception of MMP-9, the expression of which has been previously described by our laboratory) (7). As presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, administration of CC16 may be an effective treatment for COPD. Our previous study demonstrated that rCC16 inhibited the expression of COPD-contributing MMP-9 in LPS-treated RTE cells via the attenuation of NF-κB activation (7). The present study has identified a network of proteins involved in the mechanisms underlying the anti-inflammatory activity of rCC16.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations